Multiplication Wheel Learning Media Design in Mathematics Learning Material for Multiplication of Numbers in Elementary Schools - Muthma'innah, M (Rangkiang Mathematics Journal, 2024)
The mathematical abilities of second-grade elementary school students in the multiplication operation material are still relatively low. Seeing this condition, teachers must pay attention to teaching students variations in the use of learning media that invite students to play while learning so that teachers can instil the mindset that multiplication is very easy. One learning media that can be used is the multiplication wheel learning media. This research aims to describe the design of multiplication wheel learning media on number multiplication material. This research is library research. Using the multiplication wheel learning media in Mathematics subjects in class II SD/MI can improve student learning outcomes because learning activities are carried out by playing while thinking. With learning media like this, students will not get bored and bored when participating in learning activities. The multiplication wheel learning media is also very easy for lower-grade students to use. This multiplication wheel learning media is three-dimensional. Because the media does not move and does not make sound, in learning mathematics, especially in improving material, the teacher must be able to instil the mindset that addiction is very easy. Using the learning media of the accretion wheel in Mathematics in class II SD/MI can improve student learning outcomes because learning activities are carried out by playing while thinking. The existence of learning media like this will make students not bored and not bored in participating in learning activities. Improved learning media is now also very easy for low-grade students to use. This accretion wheel learning media includes three-dimensional learning media because the media does not move on its own and does not make sound.